2021
DOI: 10.1126/science.abi8358
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the catalytic conformations of an assembly-line polyketide synthase module

Abstract: Big molecules build small Actinomycete bacteria are prolific producers of bioactive small molecules such as polyketide antibiotics. These molecules are built by the addition of short carbon units to a growing, protein-tethered chain, either iteratively as in fatty acid synthesis or in a modular fashion by a hand-off from one distinct enzyme complex to the next. Bagde et al . and Cogan et al . report structures of polyketide synthase modules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
82
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 69 publications
9
82
0
6
Order By: Relevance
“…This work revealed that interdomain contacts are critical for establishing the various functional states of the module, and that transitions between such states rely on evolving interfaces between the domains, as well as the intervening ‘linker’ regions. This view of modular function was recently reinforced by cryo-EM/crystallographic analysis of additional modules sourced from two PKS systems 6 , 7 . In short, PKS modules appear to be highly integrated units, thus explaining why exchange of catalytic domains for heterologous counterparts is often detrimental 8 .…”
Section: Introductionmentioning
confidence: 95%
“…This work revealed that interdomain contacts are critical for establishing the various functional states of the module, and that transitions between such states rely on evolving interfaces between the domains, as well as the intervening ‘linker’ regions. This view of modular function was recently reinforced by cryo-EM/crystallographic analysis of additional modules sourced from two PKS systems 6 , 7 . In short, PKS modules appear to be highly integrated units, thus explaining why exchange of catalytic domains for heterologous counterparts is often detrimental 8 .…”
Section: Introductionmentioning
confidence: 95%
“…Because 1B2 did not inhibit the core catalytic activities of the module, it supported the hypothesis that the “extended” conformation is preserved throughout the catalytic cycle. Two recent Cryo-EM studies further underscore this hypothesis, both studies leveraged 1B2 and found the F ab to be crucial in their analysis [ 61 , 62 ]. The Lasalocid A PKS module (Lsd14) was determined at 2.4 (X-ray) and 3.1 Å (Cryo-EM) resolutions, respectively.…”
Section: Polyketide Synthases (Pkss)mentioning
confidence: 99%
“…Identification of neutral F ab s that bind different PKS epitopes could help resolve portions of Cryo-EM models that remain elusive. One portion of the PKS that remains especially difficult to model is the flexible TE domain [ 61 ]. The structure of a F ab that recognizes the DEBS TE (3A6, PDB ID 6MLK ) has been reported; this can be considered a neutral F ab because the TE maintains its catalytic activity as part of the complex [ 61 , 63 ].…”
Section: Polyketide Synthases (Pkss)mentioning
confidence: 99%
See 1 more Smart Citation
“…These complex structures provide detailed molecular insights into how trans-ATs recognize their ACP partners. During the preparation of this manuscript, structures of cis-AT PKS modules were reported (Bagde et al, 2021;Cogan et al, 2021). The X-ray structure of Lsd14 shows the transacylation state of apo LsdACP7.…”
Section: Introductionmentioning
confidence: 99%